CREATION OF COMIC STRIPS USING CANVA IN TEACHING WRITING TO STUDENTS - Fitria, Tira Nur (Jurusan Sastra Indonesia, 2023)
This study simulates the making of comic strips using Canva in teaching writing skills. This research utilizes descriptive qualitative. The analysis shows that creating comic strips using Canva is easy and simple. Open Canva at www.canva.com/ on mobile/ desktop then sign in or register using email, Facebook, or Google. Search for